English major students’ satisfaction with ELSA Speak in English pronunciation courses - Vi Thi Tuong Pham; Anh Tuan Pham (PLoS ONE, 2025)
Clear and accurate pronunciation plays an essential role in communicating effectively and significantly affects English learners’ proficiency. ELSA Speak has been used in some schools due to its benefits to help learners improve English pronunciation. However, to optimize the application, a better understanding of EFL learners’ satisfaction with ELSA Speak is essential. The novelty of this study is assessing how English major students were satisfied with using ELSA Speak to enhance their pronunciation and explore key factors that contributed to positive users’ experience. Two hundred and five English major students at a Vietnamese higher education institution were surveyed by a 23-item questionnaire classified into four variables: perceived usefulness, perceived ease of use, confirmation, and satisfaction. The findings recorded a high level of satisfaction among participants. Moreover, although both perceived ease of use and confirmation showed a considerable impact on learners’ satisfaction, confirmation was reported to be the determining antecedent of satisfaction. Perceived usefulness was directly influenced by perceived ease of use and had a stronger influence on confirmation compared to perceived ease of use. However, perceived usefulness did not have a directly significant correlation with learners’ satisfaction. These results can add evidence of learners’ satisfaction with using ELSA Speak, explain some elements affecting satisfaction, and suggest employing ELSA Speak in pronunciation courses with careful consideration of the content and teacher support as a facilitator.